Development of semiochemical-based tools for the management of the African citrus triozid (ACT) Trioza erytreae Del Guercio (Hemiptera: Triozidae) - Pirk, Christian Walter Werner (University of Pretoria, 2020)
Thesis (PhD (Entomology))--University of Pretoria, 2020.